The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/micr.30164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between anterolateral thigh, radial forearm, and peroneal artery flap donor site thickness in Asian patients—A sonographic study

Abstract: The RF flap was found thinner than peroneal flap, and peroneal flap was found thinner than ALT flap. The BMI effects on RF and peroneal flaps were much less than that on ALT flap. Therefore, the RF and peroneal flaps would be the better choice in obese patients with soft tissue defects where a thin flap is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
6
24
0
2
Order By: Relevance
“…Similar to our study, earlier studies have also demonstrated thicker subcutaneous fat in the anterior thigh region in female patients than in male patients [8,11,12,13], and also the ALT flap thickness has been correlated with BMI [8,11,13,14]. In the present study, we have demonstrated for the first time that there exists a correlation between flap thickness and BMI and gender in all thigh flaps studied, including the PAP flap.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our study, earlier studies have also demonstrated thicker subcutaneous fat in the anterior thigh region in female patients than in male patients [8,11,12,13], and also the ALT flap thickness has been correlated with BMI [8,11,13,14]. In the present study, we have demonstrated for the first time that there exists a correlation between flap thickness and BMI and gender in all thigh flaps studied, including the PAP flap.…”
Section: Discussionsupporting
confidence: 91%
“…Aladimi et al [7] reported a mean thickness of 14.5 ± 4.2 mm for the ALT flap; this relatively high value was probably because the volunteers in their study were all healthy and Americans. Hsu et al [8] reported a lower mean thickness of 9.8 ± 4 mm in 202 healthy volunteers from Taiwan. These data from Doppler ultrasound studies suggest that the flap thickness varies with ethnic origin and health status and it appears to be less in Asian patients than in Westerners.…”
Section: Discussionmentioning
confidence: 98%
“…Because multiple perforators could be usually found in the lateral lower leg, a double‐paddle peroneal flap could be easily harvested (Yang et al, ). With its relative thinness compared to antero‐lateral thigh flap (Hsu et al, ), the peroneal flaps could be easily reshaped into desirable shapes, such as acute‐angle mouth angle (Liu & Yang, ), hemiglossectomy defect (Lin, Liu, Lin, Chen, & Yang, ), hypopharyngeal defect (Lin et al, ), or extensive lip reconstruction (Lin, Liu, Lin, Chen, Hsueh et al, ). The novelty of this report is that we refine our design to maximize the area of skin paddle we could harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Flap thickness is thinner than that of ALT flaps (6.32 mm vs. 9.8 mm). Though LAFF is reported to be thicker than RFFF (6.32 mm vs. 2.8 mm), our experience reveals that extremely thin septocutaneous flaps can be harvested through a more lateral epicondyle oriented approach than conventional one [18,20,21]. It was especially useful for tongue tip reconstruction where thin pliable flap characteristics play bigger roles in shaping the delicate dimension of the tip, providing more functional tongue mobility.…”
Section: Discussionmentioning
confidence: 89%